Absence from day care or school and parental absence from work during children's respiratory infections. (22nd December 2022) - Paalanne, Marika; Honkila, Minna; Paalanne, Niko; Mattila, Suvi; Pokka, Tytti; Renko, Marjo; Tapiainen, Terhi
Abstract: Aim: To investigate the social burden of nasopharyngeal detection of various respiratory viruses and the co‐detection of viral and bacterial pathogens. Methods: This prospective cohort study included 737 children with a suspected respiratory tract infection or fever in a paediatric emergency department during one epidemiological year (2014–2015) in Finland. Nasopharyngeal swab samples were analysed with multiplex polymerase chain reaction for 16 viruses and 7 respiratory bacteria. Parents filled out a questionnaire regarding child's and parents' absence from day care, school, or work at the time of the visit and 14 days afterward. Results: The length of the children's absence from day care or school, or parental absence from work, did not significantly differ between the detected viral pathogens. Co‐detection of any respiratory virus and Streptococcus pneumoniae or Haemophilus influenzae in the nasopharynx were associated with a 2.5‐day (95% CI of the difference: 0.71 to 4.3) and 3.0‐day (95% CI: 0.35 to 5.7) longer parental absence from work, respectively, compared with the detection of viruses alone when adjusted for age. Conclusion: Nasopharyngeal detection of S. pneumoniae or H. influenzae was associated with an increase in the length of parental absence from work when compared with the detection of virus alone.